Performance of thermoelectric cooler powered by photovoltaic cell with and without cooling method - Kuek, Wee En (2022)
Solar powered thermoelectric refrigerator is a refrigerator that makes use of solar energy for electrical energy conversion to supply power to the thermoelectric module based on the principle of Peltier’s effect. The working principle of the solar powered refrigerant is based on thermoelectric module which creates a hot side and cold side when it is supplied with electrical energy produced by the solar module. The cooler region of the thermoelectric module is used for cooling purpose while the heat produced on the hotter region is rejected to the ambient surroundings by the fans and heat sink which is the active and passive cooling method. This project is aimed to study and build a prototype of thermoelectric cooler powered by photovoltaic cell to produce refrigeration effect for cooling purpose. A simulation software (ANSYS) was used for heat transfer evaluation on the surface of the photovoltaic cell and heat flow of cooling air for analysis purpose. Water cooling method and air cooling method were applied in simulation work, then validated in experimental work. Theoretical calculation was done for the cooling load required to achieve the targeted temperature in the refrigerant area. The results showed the air cooling method provided a lower performance and achieved lower efficiency for the thermoelectric module compared to that of the water cooling method. The water cooling method produced the temperature inside the chiller box at 13°C while the temperature distributed on the surface of photovoltaic panel was 40.3°C. Comparatively, the air cooling method produced the temperature inside the chiller box at 12.5°C while the temperature distributed on the surface of photovoltaic panel was 27.1°C. Moreover, the non cooling method produced the temperature inside the chiller box at 11.5°C while the temperature distributed on the surface of photovoltaic panel was 22.4°C